Immunotherapy after progression to double immunotherapy: pembrolizumab and lenvatinib versus conventional chemotherapy for patients with metastatic melanoma after failure of PD-1/CTLA-4 inhibition - Lyrarakis, Georgios; Liontos, Michael; Anastasopoulou, Amalia; Bouros, Spyridon; Gkoufa, Aikaterini; Diamantopoulos, Panagiotis; Gogas, Helen; Ziogas, Dimitrios C. (Frontiers in Oncology, 2024)
BackgroundProgrammed cell death 1 receptor (PD-1) inhibition as monotherapy followed by Cytotoxic T-lymphocyte associated protein 4 (CTLA-4) inhibition in case of progression or as upfront double co-inhibition has drastically improved the survival outcomes of metastatic melanoma. Still, many patients develop primary or acquired resistance to both agents, relapse soon, and survive less. For these patients, the therapeutic options are very limited, and for many years, conventional chemotherapy (CC) was the standard of care. Recently, the phase II LEAP-004 trial supported that pembrolizumab/lenvatinib could potentially overcome anti-PD-1/anti-CTLA-4 immunotherapy refractoriness.Materials and methodsIn the absence of any prospective comparative study and to evaluate in a real-world context the clinical benefit of re-administering a PD-1 inhibitor (pembrolizumab 200 mg i.v. every 3 weeks, Q3W) with a multi-kinase inhibitor (lenvatinib, but at a reduced dose 10 mg p.o. daily due to its known toxicity) in this frail population of unmet need, we conducted here a retrospective comparison of LEAP-004-proposed combination with CC (carboplatin 4 AUC and dacarbazine 850 mg/m2 i.v. Q3W) in melanoma patients who relapsed to both checkpoint inhibitors, either in combinatorial or in sequential setting, between July 2022 and January 2024. Baseline demographics, disease characteristics, and treatment outcomes (objective response rate (ORR), progression-free survival (PFS), and overall survival (OS)) were recorded. Survival analyses were performed using the Kaplan–Meier method. All patients were also considered for safety analysis.ResultsA total of 84 patients were included in the effectiveness and safety analysis (pembrolizumab/lenvatinib, n=39 and CC, n=45). The median age was 67 (45–87) years and 64 (34–87) years, and men were 33.3% and 46.7%, respectively. The distribution of their metastatic sites was comparable, including 12.8% and 20% with brain involvement. Most patients had a good PS<2 (69.9% and 56.5%), increased lactate dehydrogenase (LDH) (71.8% and 84.4%), BRAF-wild status (82.1% and 84.8%), and received ≥2 previous systemic therapies (61.5% and 53.3%). The median follow-up was 18 months. The ORR was 23.1% and 11.1% (p<0.0001), the median PFS was 4.8 months and 3.8 months [HR (95%CI), 0.57 (0.36–0.92); p=0.017], and the median OS was 14.2 months and 7.8 months [HR (95%CI), 0.39 (0.22–0.69), p=0.0009] in pembrolizumab/lenvatinib and CC arms, respectively. Grade 3–5 treatment-related adverse events were documented in 48.7% (pembrolizumab/lenvatinib) and 75.6% (CC) of patients (p=0.034), which led to treatment discontinuation in 10.3% and 17.8% of cases, respectively.ConclusionsThis is the first comparative study in patients with metastatic melanoma refractory to PD-1/CTLA-4 inhibition and showed significantly longer outcomes in cases treated with pembrolizumab/lenvatinib versus CC.